The Effect of Compensation, Organizational Culture, and Rewards on Employee Productivity in Retail Companies in Indonesia - Wahdiniawati, Siti Annisa; Immamah, Eka (Westscience Press, 2024)
This study examines the effect of compensation, organizational culture, and rewards on employee productivity in retail companies in Indonesia. Using a quantitative research design, data were collected from 140 retail employees and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The findings reveal that compensation, organizational culture, and rewards all have significant positive effects on employee productivity. Compensation emerged as the strongest predictor, followed by organizational culture and rewards. These results suggest that fair compensation, a supportive organizational culture, and effective reward systems can significantly enhance employee performance in the retail sector. The study provides practical recommendations for retail companies to improve workforce productivity through strategic human resource management.